The Mousetrap of Language: The Mechanism of Anamorphosis in the Works of Edgar Allan Poe and Antun Gustav Matoš - Milanko, Andrea; Tomljenović, Ana (Poznańskie Studia Slawistyczne, 2023)
Rethinking conditions of revolutionary potential of literature, with special regard to ways literature incessantly has re-examined otherness in language, in this paper we have chosen to focus on specific mechanism of illusion-making, i.e. anamorphosis taken both as a technique and a theme. Since one of the most famous elaboration of anamorphosis in literature is to be found in Poe’s stories, it is worthwhile to examine how Poe’s game of hide and seek with depth and surface is reflected in his devoted Croatian reader and interpreter A.G. Matos. In a comparative analysis of Poe’s and Matos’s stories, we will elaborate on how a procedure of naming and a procedure of signifying are revealed to be mere effects of anamorphosis in Matos’s short story “Miš” (The Mouse). Since it is an embodiment of a figure designating schism and split, the rodent from the title of Matos’s short story reveals the other side of thinking, which is no other than the other within.